172k views
2 votes
Of the following options, what could be a possible first step in solving the equation x + 6 = 3x -2

User DuCorey
by
4.6k points

2 Answers

7 votes

Answer:

subtracting 6 from both sides

Explanation:

User Zhnglicho
by
5.1k points
2 votes

Explanation:

X + 6 = 3x - 2

Bringing like terms on one side

6 + 2 = 3x - x

8 = 2x

8/2 = x

4 = x

User Jegadesh B S
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.